Sonic Hedgehog Signaling Regulates Hematopoietic Stem/Progenitor Cell Activation during the Granulopoietic Response to Systemic Bacterial Infection - Shi, Xin; Wei, Shengcai; Simms, Kevin J.; Cumpston, Devan N.; Ewing, Thomas J.; Zhang, Ping (Frontiers in Immunology, 2018)
Activation and reprogramming of hematopoietic stem/progenitor cells play a critical role in the granulopoietic response to bacterial infection. Our current study determined the significance of Sonic hedgehog (SHH) signaling in the regulation of hematopoietic precursor cell activity during the host defense response to systemic bacterial infection. Bacteremia was induced in male Balb/c mice via intravenous injection (i.v.) of Escherichia coli (5 x 107 CFUs/mouse). Control mice received i.v. saline. SHH protein level in bone marrow cell (BMC) lysates was markedly increased at both 24 and 48 h of bacteremia. In contrast, the amount of soluble SHH ligand in marrow elutes was significantly reduced. These contrast alterations suggested that SHH ligand release from BMCs was reduced and/or binding of soluble SHH ligand to BMCs was enhanced. At both 12 and 24 h of bacteremia, SHH mRNA expression by BMCs was significantly up-regulated. This upregulation of SHH mRNA expression was followed by a marked increase in SHH protein expression in BMCs. Activation of the ERK1/2-SP1 pathway was involved in mediating the upregulation of SHH gene expression. The major cell type showing the enhancement of SHH expression in the bone marrow was lineage positive cells. Gli1 positioned downstream of the SHH receptor activation serves as a key component of the hedgehog pathway. Primitive hematopoietic precursor cells exhibited the highest level of baseline Gli1 expression, suggesting that they were active cells responding to SHH ligand stimulation. Along with the increased expression of SHH in the bone marrow, expression of Gli1 by marrow cells was significantly up-regulated at both mRNA and protein levels following bacteremia. This enhancement of Gli1 expression was correlated with activation of hematopoietic stem/progenitor cell proliferation. Mice with Gli1 gene deletion showed attenuation in activation of marrow hematopoietic stem/progenitor cell proliferation and inhibition of increase in blood granulocytes following bacteremia. Our results indicate that SHH signaling is critically important in the regulation of hematopoietic stem/progenitor cell activation and reprogramming during the granulopoietic response to serious bacterial infection.